(untitled) (Stato, Chiese e pluralismo confessionale, 2012)
Contributo sottoposto a valutazione. SOMMARIO: 1. Limits to free speech, incitement to hatred and a “third case” - 2. UN Resolutions on Defamation of Religions (1999 – 2010). The role of the Organization of Islamic Cooperation - 3. Recognizing values and rights in the defamation of religions discourse - 4. The interplay between racial and religious offences and its effect on limitations to free speech - 5. Balancing freedom of expression and freedom of religion in the work of the UN Human Rights Committee - 6. Concluding Remarks. ABSTRACT: Freedom of religion, freedom of expression and the United Nations: recognizing values and rights in the “defamation of religions” discourse (Lecturer in Law and Religion, University of Perugia) The article focuses on the issue of religious freedom and freedom of expression from the point of view of the United Nations. In particular, it examines the so called Defamation of religions, which has been the topic of a series of Resolutions voted by the Human Rights Commission, the Human Rights Council and the Assembly General, from 1999 to 2010. In the Defamation of religions debate, the UN institutions appear to tend to highlight the conflict between rights rather than the positive interrelation between them. Nonetheless, it has been repeatedly argued that it should be possible for political institutions and religious majorities to use anti-defamatory legislation in order to stem the activities of religious minorities. Applying penal anti-defamation laws might not be the best way to deal with the potential conflict between two fundamental rights. The more recent trends show a shift toward what seems to be a more suitable accommodation of the interests at stake. In this regard, the article will consider the Human Rights Council’s Resolution about discrimination on religious grounds (2011), the Ad Hoc Committee on Complementary Standards to the ICERD and the new General Comment on article 19 of the ICCPR.